Effective tricuspid regurgitation reduction is associated with renal improvement and reduced heart failure hospitalization - Felbel, Dominik; von Winkler, Juliana; Paukovitsch, Michael; Gröger, Matthias; Walther, Elene; Andreß, Stefanie; Schneider, Leonhard; Markovic, Sinisa; Rottbauer, Wolfgang; Keßler, Mirjam (Frontiers in Cardiovascular Medicine, 2024)
Background Several studies have demonstrated an association between tricuspid regurgitation (TR) and organ dysfunction including hepatic and renal insufficiency. Improvement of liver function following transcatheter edge-to-edge repair (T-TEER) has already been linked to reduction of venous congestion due to TR reduction. This study analyzes whether TR-reduction using T-TEER is also associated with improved renal function. Methods and results The TRIC-ULM registry includes 92 selected patients undergoing T-TEER between March 2017 and May 2023. Estimated glomerular filtration rate (eGFR) improvement was evident in 53 patients (57%) at 3-months follow-up (FU) and defined by FU eGFR > baseline eGFR. Median age was 80 [interquartile range 75–83] years, pre- and postinterventional TR grades were 4 [3–5] and 1 [1–2], baseline eGFR was 36 [30–53] ml/min and New Yeark Heart Association (NYHA) IV was evident in 15% of patients. Multiple logistic regression analysis revealed TR vena contracta reduction (Odds ratio (OR) 1.35 [95% CI: 1.12–1.64] per mm, p = 0.002) and reduced preinterventional tricuspid annular plane systolic excursion (TAPSE) [OR 0.89 (95% CI: 0.79–0.99) per mm, p = 0.033] to independently predict renal improvement at FU. An eGFR improvement threshold of >9 ml/min was associated with reduced 1-year heart failure hospitalization rates [adjusted hazard ratio 0.22 (95% CI: 0.07–0.62) p = 0.005]. Conclusion Effective tricuspid edge-to-edge repair is associated with improved renal function and reduced heart failure hospitalization. In patients without renal improvement at 3-months follow-up, residual tricuspid regurgitation should be reevaluated for reintervention.